Thermodynamic of the f(Q) universe - Haomin Rao; Chunhui Liu; Chao-Qiang Geng (European Physical Journal C: Particles and Fields)
Abstract We investigate thermodynamics of apparent horizon in the f(Q) universe with trivial and nontrivial connections. We first explore the perspectives of the first law, generalized second law and P–V phase transition with trivial connection. We show that the lowest-order correction of entropy has the same form as that in loop quantum gravity, and the critical exponents of the phase transition caused by the lowest-order correction are consistent with those in mean field theory. We then examine the thermodynamic implication of nontrivial connections. We find that nontrivial connections in the f(Q) universe imply non-equilibrium states from the perspective of thermodynamics.